Indigenous education at university: Stepping into and navigating the classroom - Rom, Mitchell (The Australian Journal of Indigenous Education, 2023)
This article provides a critical insight into some of the key challenges that are found in Indigenous education at university. It achieves this through sharing the storied experiences of non-Indigenous pre-service teachers, academics and myself. Overall, the study found, through storying methodology, a total of 11 key challenges across interrelated areas of the university. These areas included the university classroom and the broader institution, as well as education policy, specifically the Australian Professional Standards for Teachers (APST) 1.4 and 2.4 by the Australian Institute for Teaching and School Leadership (AITSL). This paper will provide an in-depth insight into three key classroom challenges (1, 2 and 4). It will not address key institutional or policy challenges. Ultimately, this paper will argue that some schools in Queensland need to place a greater value on the inclusion of Indigenous knowledges and perspectives. A practical recommendation is also offered in this article to further strengthen Indigenous education at university.